KAJIAN FILOSOFIS TRADISI PITONAN DI DESA RINGINPITU KECAMATAN KEDUNGWARU KABUPATEN TULUNGAGUNG JAWA TIMUR (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
This pitonan tradition is intended for children who are setting their feet on the ground for thefirst time. In the implementation of this tradition there are many symbols such as climbing thejadah, climbing stairs made of sugar cane, entering a chicken cage, bathing using setamanflowers, spreading udhik-udhik and cutting tumpeng. This tradition is usually carried out whenthe baby is 7 months old on the Javanese calendar. This 7 month old baby is usually markedby starting to crawl. Based on this background, several problems were formulated as follows:1) What is the form of the pitonan tradition in Ringinpitu Village, 2) What is the function of thepitonan tradition in Ringinpitu Village, 3) What is the meaning of Hindu philosophy containedin the pitonan tradition in Ringinpitu Village. Researchers use 2 theories to dissect existingproblem formulations as follows: 1) Religious Theory, 2) Symbol Theory. The form of thePitonan tradition consists of the following: the time for implementing the Pitonan tradition iscarried out when the baby is 7 months old, marked by the baby starting to crawl, in theprocession of implementing the Pitonan tradition, it goes through several stages such asundressing, climbing stairs, entering the chicken cage, bathing in setaman flower water andpapacan, kenuren. The Pitonani tradition also uses several facilities such as chicken cages,setaman flower water, sugar cane ladders, chicken ingkung, various rice and accompaniments,various porridge and market snacks, plantains, cok bakal, coins and yellow rice, and jadah.Apart from being used to save babies, the Pitonan tradition also functions as a means ofstrengthening relationships between relatives and also functions as a cultural preservation.This tradition also contains many moral values such as respecting parents and loving God'sanimals. In the implementation of the Pitonan tradition, several facilities are required to beseven, such as the stairs to be climbed have seven steps which describe the level of life andeducation that will be passed, apart from that there are also seven jadah where each color hasits own meaning, then The water and flowers used to bathe the child each come from sevensprings and seven types of flowers
Keywords: pitonan tradition, philosophy